THE EFFECT OF COMPETENCY DEVELOPMENT AND EMPLOYEE WELL-BEING ON EMPLOYEE PERFORMANCE IN FURNITURE COMPANIES IN WEST JAVA, INDONESIA - Ardana, Raffi; Putri, Vivi Amelia; Alwi, Muhamad (Syntax Literate, 2025)
This study examines the influence of competency development and employee welfare on employee performance on CV. Agung Jaya Putra Furniture in Cirebon, West Java. The problem raised is the gap between employee competence, the demands of the modern furniture industry, and welfare programs that are not optimal in increasing motivation and work productivity. The research used a quantitative approach with a saturated sample of 103 employees. Data was collected through a questionnaire with a Likert scale and analyzed using Structural Equation Modelling (SEM) with SmartPLS 4. The variables studied include competency development, employee welfare, and employee performance. The results showed that the model could explain 66.1% of the variation in employee performance. Hypothesis testing revealed that employee welfare and competency development had a positive and significant effect on employee performance, with competency development having a stronger influence (F-squared 0.424) than employee welfare (F-squared 0.050). In conclusion, companies need to pay more attention to employee competency development programs, ensure the effectiveness of wellness programs, and adopt a holistic approach to improving employee performance. This research makes an important contribution to understanding the dynamics of human resources in the furniture industry, but generalizing the results must be done carefully, given the limitations of research on a single company.